3rd Generation Alumina-on-Alumina in Modular Hip Prosthesis: 13 to 18 Years Follow-up Results. Issue 1 (January 2017) - Toni, Aldo; Giardina, Federico; Guerra, Giovanni; Sudanese, Alessandra; Montalti, Maurizio; Stea, Susanna; Bordini, Barbara
Introduction: Ceramic-on-ceramic (CoC) couplings are alternative bearings surfaces that have been reported to reduce osteolysis, wear debris and aseptic loosening compared to the use of polyethylene. Early experiences with ceramics had poor results, but they have led to many improvements in the manufacture and design of subsequent implants. Methods: We analysed medical files of 300 CoC total hip arthroplasty (THA) with a modular neck performed during period 1995-2000 by a single surgeon for a minimum follow-up of 13 years, evaluating clinical and radiological outcome. Results: The mean clinical Merle d'Aubigne and Postel hip score at the final follow-up is 17.4, against a pre-operative value of 11.4. Overall survivorship with an endpoint of revision is 93.2% (95% CI, 89.0%-97.3%) at 15 years, while considering only prosthesis failures related to aseptic loosening and ceramic breakage, survival rate at 15 years is 97.2% (95% CI, 94.8%-100%). We observed complications that led to revision surgery in 11 patients (4%) (periprosthetic fractures, liner ruptures, septic loosening of the implant, aseptic loosening of the cup, aseptic loosening of the stem). The occurrence of squeaking is low (1.6%, 4 cases) and we analysed the characteristics of these patients. Discussion: Our study shows an excellent long term survivorship of third generation alumina CoC THA. We reiterate the importance to have a stable implant to maximise the advantage of ceramic and to avoid complications.